International market penetration by Japanese affiliates via exporting from ASEAN4 and China - Yong, C.C.; Yew, S.Y.; Mizuno, K.; Teh, P.L. (2011)
Bayesian analysis is used to perform the probability estimation to examine the Japanese affiliates’ market penetration by exporting from ASEAN4 (i.e. Indonesia, Malaysia, Philippines and Thailand) and China. The estimation is conducted for 13 manufacturing sub-sectors in 2001-2005 and 2006-2010. This study found that Japanese affiliates not only benefited from low cost production and low trade barriers but also seized the advantage of internalized global production network within ASEAN4 and China to export their goods. Production networking could have both favorable and adverse effects on exports of Japanese affiliates.